The Effect of Government Capital Expenditure on Banking Credit in KDT Regency (Lake Toba Region) - Amelira Haris Nasution; Mangasa Augustinus Sipahutar; Aldon MHP Sinaga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The beauty of Lake Toba in North Sumatera makes Lake Toba one of the five Super Priority Destinations (DSP) promoted by the government in tourism development. This stipulation is expected to be able to improve the economy of the Lake Toba (KDT) region which is geographically inhabited by 7 (seven) sub-districts, which are directly adjacent to North Tapanuli Regency, Toba Regency, Simalungun Regency, Dairi Regency, Karo Regency, Humbang. Hasundutan Regency and Samosir Regency. The purpose of this study was to find out and analyze the answers related to the effect of government capital expenditure on bank credit around KDT Regency. The data used is secondary data in the form of time series data in KDT for the period 2000–2019 regarding the economic sector GRDP, bank credit and government capital expenditures. Data processing uses the E-Views 10 application through panel data analysis using data on the ratio of government capital expenditure and bank credit to nominal GRDP in all KDT areas. Based on the results of the analysis, the results of the variable ratio of government capital expenditure to nominal GRDP have a positive and significant effect of 0.161587 on banking credit to nominal GRDP from 2005 to 2019 in the KDT area. This shows that there is a relationship and influence of capital expenditure on banking credit in the KDT area during 2005-2019, which means that capital expenditure and the banking sector will be able to become a driver of economic growth, including in the development of the KDT area.